2014
DOI: 10.1589/jpts.26.633
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neuromuscular Electrical Stimulation on the Heart Rate Variability in Healthy Subjects

Abstract: [Purpose] The purpose of this study was to examine the effect of neuromuscular electrical stimulation (NMES) on heart rate variability (HRV). [Subjects and Methods] Ten healthy subjects participated in the study. All subjects received NMES with a pulse duration of 300 us and frequency of 30 Hz at the vastus lateralis and vastus medialis for 15 minutes. The stimulation intensity was adjusted in the range of 20 to 30 mA. HRV using a pulse oximeter was measured in the sitting position before and after NMES. [Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…There were no unanticipated effects on the cardiovascular system during any of the trials (Table 1 and 2). This supports previous NMES research using maximal tolerable intensities 53,54 and BFR research using 70% BFR pressures 55,56 . In agreement with the current findings, no adverse events have occurred in healthy and spinal cord-injured adults previously [11][12][13][14] .…”
Section: Discussionsupporting
confidence: 89%
“…There were no unanticipated effects on the cardiovascular system during any of the trials (Table 1 and 2). This supports previous NMES research using maximal tolerable intensities 53,54 and BFR research using 70% BFR pressures 55,56 . In agreement with the current findings, no adverse events have occurred in healthy and spinal cord-injured adults previously [11][12][13][14] .…”
Section: Discussionsupporting
confidence: 89%
“…35,36 In contrast, several studies have suggested changes in autonomic activity and cardiovascular response when subjects performed RT or NMES alone. 18,19,37 This study did not show that adding NMES to RT elicited a worse response to autonomic activity or cardiovascular response compared to RT alone. The results from this study support the safety of RT þ NMES, as shown in the results of previous studies investigating RT or NMES alone from the aspect of evaluating autonomic activity and cardiovascular response.…”
Section: Discussionmentioning
confidence: 54%
“…A previous study has shown that electrical stimu- lation can modulate the sympathetic and parasympathetic activity of nerves 30 . However, other authors have demonstrated that electrostimulation in muscles of vastus lateralis and vastus medialis was not able to acutely affect HRV in healthy individuals 32 . In the present study, participants received NMES in more muscle groups in addition to performing an associated dynamic exercise protocol.…”
Section: Acute Effects Of Wb-ems On Hrv Indexesmentioning
confidence: 91%